Incidence of wisents in hunting grounds leased by hunting clubs in Bieszczady (European Bison Conservation Newsletter, 2015)
Analyzed were effects of wisents’ Bison bonasus presence within hunting grounds administered by Polish Hunting Association. At present wisents live in 8 such units at the total area of about 18 thousand ha. Total damages caused by wisents were estimated there in 2014 for about 15 thousand PLN that included costs of grazed or damaged plants grown for supplemental feeding, eaten fodder from game feeders and destroyed or utilized salt licks. Lack of financial support from sources available for State Forests results in negative attitude of hunters towards wisents’ presence.
Keywords: European bison; damages; acceptance for protected species